PENGARUH STRES TERHADAP KEJADIAN INSOMNIA DI MASA PANDEMI COVID - 19 PADA MAHASISWA FK UMSU - RAUDATUL HUSNA PRANATA; ROBITAH ASFUR (LP2MTBM MAKARIOZ, 2021)
A significant impact is felt by students because the learning process is different as usual, assignments and exams are carriedout online, where the learning process requires good preparation, besides non-academic factors such as excessive fear ofcontracting the COVID-19 virus which tends to be psychosomatic, These things can be categorized as stressors that causestress that triggers insomnia or disturbances in sleep patterns in students. This study is a correlative analytic study todetermine the relationship or correlation of a variable with other variables with a cross sectional approach with 50respondents from the Faculty of Medicine, University of Muhammadiyah Sumatera Utara. Univariate analysis was carried outon each research variable and category of the frequency distribution of each variable, Most of the students experiencedmoderate stress levels, as many as 31 people (62%), 28 students (56%) experienced insomnia, there was a relationshipbetween stress levels and the incidence of insomnia and the results obtained p- value: 0,000. Most of the studentsexperienced moderate stress and experienced sleep disturbances, namely insomnia. There is a relationship between stressduring the pandemic and the incidence of insomnia.